Multi-cracks detection of a beam-like structure based on the on-vehicle vibration signal and wavelet analysis - Nguyen, Khoa Viet; Tran, Hai Thanh (Journal of sound and vibration, 2010)
In this paper, a new method for detecting a multi-cracked beam-like structure subjected to a moving vehicle is presented. The crack model is adopted from fracture mechanics. The dynamic response of the bridge–vehicle system is measured directly from the moving vehicle. When moving along the structure, the moving vehicle causes small distortions in the dynamic response of the bridge–vehicle system at the crack locations. In general, these small distortions are difficult to detect visually. However, wavelet transform has recently emerged to be an effective method of detecting such small distortions. Large values (peaks) in the wavelet transform indicate the existence of the cracks. The locations of the cracks are pinpointed by positions of peaks of the wavelet transform and the velocity of the moving vehicle. Numerical results show that the method can detect cracks as small as 10% of the beam height. The proposed method is applicable for low velocity-movements while high velocity-movements are not recommended. The method presents an idea for measuring the vibration directly from the vehicle for crack detection problem in practice.